Extending the indications for intraoperative transesophageal echocardiography - Brykczyński, Mirosław; Listewnik, Mariusz J.; Mokrzycki, Krzysztof; Jędrzejczak, Tomasz (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2010)
Intraoperative transesophageal echocardiography (ITEE) is advised and renowned tool for diagnosis, operation planning and immediate verification of the procedure effect. It has became a golden standard for valve surgeries and aortic aneurysm correction procedures, but lately the indications for TEE are expanding, thanks to its minimal invasive character and good reliability. Introduction of the new operation techniques, common use of femoral cannulation for CPB and use of mechanical circulatory support systems has raised the needs for TEE in cardiac surgery centers in last years. Nowadays, modern center of cardiac surgery without the constant access to echocardiographic diagnostics is hard to imagine. However, there is not enough qualified personnel (anestesiologists or cardiologists) to secure the needs of urgent surgeries. Therefore, after the analysis of the Clinic own material, we state that the only solution to his problem can be training cardiac surgeons in this skill, and furthermore, there is a need for center of certification in ITEE for cardiac surgery purposes.